A quadratic semidefinite relaxation approach for resource allocation in orthogonal frequency division multiple access - Adasme, Pablo; Lisser, Abdel; Soto, Ismael (Networks, 2012)
This paper proposes two binary quadratically constrained quadratic programs for minimizing power subject to bit rate and subcarrier allocation constraints over wireless orthogonal frequency division multiple access. The first model represents a restricted case in which users are allowed to use only one modulation size in each subcarrier while the second, a more flexible real case in which they can use any size. We propose two semidefinite programming relaxations and compare with the linear programs obtained by applying Fortet linearization method. Numerical results show a total average tightness gain of 42.78 and 97.17% for the first and second quadratic model, respectively. Moreover, we get in average, near optimal lower bounds of 0.5 and 1% for the second model over random and realistic data, respectively. © 2011 Wiley Periodicals, Inc. NETWORKS, 2012